The Effectiveness of the use of Assemblr Edu-Based Augmented Reality Media on Student Learning Motivation - Nurindah; St.Hajar; Akram (Universitas Pendidikan Ganesha, 2025)
The low motivation of students to learn in science learning is caused by the limitations of interesting and interactive learning media. This is the fundamental problem behind this research. This study aims to analyze the influence of the use of Assemblr Edu's Augmented Reality (AR) digital media on students' learning motivation in science learning. The study used a quantitative approach with a pre-experimental design of one-shot case study on 51 students. Data collection techniques include observation sheets of learning activities, learning motivation questionnaires, and response questionnaires to media use. Data analysis uses descriptive and inferential statistics. The results of the study showed that 76.47% of students had learning activities in the very good category based on the results of observations. A total of 92.16% of students rated the media very positively on the use of AR Assemblr Edu digital media, and 96.08% of students showed excellent learning motivation. Hypothesis testing produced a correlation coefficient of 0.867 with a determination coefficient of 75.17%, indicating a significant and positive influence between the use of AR Assemblr Edu media and student learning motivation. This research shows that the use of AR technology in learning can be an effective solution to increase student engagement and learning motivation, as well as open up opportunities for the development of other immersive technology-based learning media in the context of science education.